General Principles of Good Government on the Competence of Government Apparatus in Making State Administration Decisions - Razak, Askari (Universitas Ekasakti, 2023)
This research will focus on specific aspects in PTUN decisions that can act as a guide for government officials in improving the quality of administrative decision making. Investigating the impact of PTUN decisions on changes or improvements to administrative policies within government officials is also the aim of this research. This research will identify potential gaps between PTUN decisions and administrative decision-making practices by government officials, as well as analyze the implications of these gaps for their competence. Furthermore, this research will examine how participation and coordination between government officials and legal institutions such as PTUN, can contribute to enriching the process of making better administrative decisions. The research method used is the normative juridical method. It is hoped that the results of this research will provide new insight into the importance of collaboration between government officials and legal institutions in improving the quality of administrative decision making in Indonesia.